Tuesday

March 31, 2015

March 31, 2015

Posted by **Lexi** on Monday, November 22, 2010 at 11:13am.

- College Algebra -
**Reiny**, Monday, November 22, 2010 at 12:00pma(x + 2y) − b(2x − y) = -4x + 12y

ax + 2ay - 2bx + by = -4x + 12y

x(a-2b) + y(2a + b) = -4x + 12y

so a-2b = -4

and 2a + b = 12

first one times 2 ---> 2a - 4b = -8

second one ----> 2a + b = 12

subtract them: -5b = -20

b = 4

back in first: a - 8= - 4

a = 4

check:

4(x+2y) - 4(2x-y)

= 4x + 8y - 8x + 4y

= -4x + 12y , checks!

- College Algebra -
**Lexi**, Monday, November 22, 2010 at 3:44pmawesome thanks!

**Answer this Question**

**Related Questions**

algebra help!!!! - Add: b^−3 ca^−1 −xc^−2 how would i do...

statistics - Use Excel to find the p-value for each test statistic.a. Right-...

biology - Given the part of the molecule shown below, can the underlined atom ...

statistics - Find the p-value for each test statistic. a. Right-tailed test, z=+...

calculus - Find an equation for the surface consisting of all points P(x, y, z) ...

STATS - Suppose we want to test the null hypothesis H0 : ì = 400 against H1 :ì &...

algebra - Which of the following is equivalent to the expression (t2 − t...

STATS (PLEASE CHECK) - 16-To test the hypothesis H0 : ì = 100 against H1 : ì >...

Grade 12 Calculus - Evaluate each of the following. Show all your calculations...

math - Could someone please tell me if I am on track with my answer? Jack is ...